2014
DOI: 10.1111/1467-9566.12163
|View full text |Cite
|
Sign up to set email alerts
|

Trust in health care encounters and systems: a case study of British pensioners living in Spain

Abstract: Research on trust in health care faces two enduring challenges. Firstly, there are conceptual ambiguities in distinguishing trust from related concepts, such as confidence or dependence. Second, the tacit understandings which underpin the ‘faith’ element of trust are difficult to explicate. A case study of British pensioners who have moved to Spain provides an opportunity to explore trust in a setting where they often have a choice of where to access health care (UK or Spain), and are therefore not in a state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 24 publications
1
24
1
Order By: Relevance
“…Naturally, the longer one stays, the more chances one might have to get to know a good doctor or a hospital by word of mouth, and more importantly, from one's own experiences. A study suggested trust in foreign healthcare was built on experiential encounters with speci c institutions; speci cally, interpersonal qualities of practitioners (respect for older people, empathy and reciprocity) and clean, modern and e cient facilities [36]. Medical facilities that most of the Japanese go to are JCI accredited and considered to meet the criteria above.…”
Section: Discussionmentioning
confidence: 99%
“…Naturally, the longer one stays, the more chances one might have to get to know a good doctor or a hospital by word of mouth, and more importantly, from one's own experiences. A study suggested trust in foreign healthcare was built on experiential encounters with speci c institutions; speci cally, interpersonal qualities of practitioners (respect for older people, empathy and reciprocity) and clean, modern and e cient facilities [36]. Medical facilities that most of the Japanese go to are JCI accredited and considered to meet the criteria above.…”
Section: Discussionmentioning
confidence: 99%
“…The focus on migrants as newcomers to the welfare state enables us to study the individual interpretations of and the meanings extracted from these meetings in a distinct way, as it opens up for reflection that would otherwise be hindered by tacit knowledge (Legido-Quigley, McKee, & Green, 2014). It can be argued that this particular empirical case, that is, migrants in Denmark, is particularly likely to exhibit trust-building processes.…”
Section: Storm M and Edwards A (2013) Models Of User Involvement mentioning
confidence: 99%
“…Research in the field of the medical professions tends to back up this claim-in this strand of research the role of the professional in the meeting with the citizen is emphasized in terms of both client trust and the emergence of institutional or system trust in health care institutions in particular (Brown, 2009;Legido-Quigley et al, 2014).…”
Section: Theoretical Background and The State Of Researchmentioning
confidence: 99%
“…However, very few researchers have been interested in what factors make people trust a welfare state and its institutions and which mechanisms create this trust. In shedding light on these questions migrants constitute a very interesting case: being in a new context both creates the necessity for the individual to reflect on otherwise tacit knowledge (Legido-Quigley et al, 2014) and requires some kind of handling of the "new" institutional setting on the other. The purpose of this article is therefore to study how people who have migrated from a broad range of countries to one destination country view the welfare state institutions there: will they develop trust in them and what are the underlying mechanisms behind this?…”
Section: Introductionmentioning
confidence: 99%